Antibiotic susceptibility and genotyping by RAPD of Campylobacter jejuni isolated from retailed ready-to-eat sushi - Tan, Yee Fen; Haresh, Kumar Kantilal; Chai, Lay Ching; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
A study to determine the antibiotic sensitivity pattern and genotyping using RAPD-PCR was performed on 50 C. jejuni isolated from sushi retailed in different supermarkets. With less than half of the isolates susceptible to the antibiotics tested, resistant to two or more antibiotics were observed in most of the isolates. The banding patterns obtained from RAPD-PCR revealed that no predominant clone exists and the bacterial population is rather diverse. Hence, the resistance of the C. jejuni to different classes of antibiotic as well as their diverse genotypes suggests that these C. jejuni isolates were generated from different sources in the contaminated supermarkets where sushi were retailed. Our data showed that C. jejuni can be an important reservoir for resistance genes and that study with comprehensive collections of samples are urgently required to establish better measures to reduce or eliminate the risk from antibiotic resistant and pathogenic bacteria originating from minimally processed ready-to-eat food.